Sobre palavras e atos no consumo sustentável no Brasil:: os ‘aparentes paradoxos’ de uma pesquisa qualitativa (Sustainability in Debate, 2013)
This article analyses some results of a broader research project called Choices Project: LeveragingBuying Power for Development - Ethical Consumption and Sustainable Procurement in Chile andBrazil-aims to “shed light” on some “apparent paradox” found in the speeches of Braziliansinterviewed in a qualitative research and analyzing contradictions between their discourses andpractice on sustainable consumption. Therefore, the article presents Brazilian political andinstitutional background for sustainable development with a focus on consumption, the apparentcontradictions found in the research and its analysis and concludes with the challenges thatindicate aspects for consideration in establishing a conscious consumption policy as part of abroader sustainable development policy capable of redesign the urban network and ensureprosperity and quality of life for all.